PENGARUH INTELEGENSI, TASK COMMITMENT DAN SELF EFFICACY TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMA - Nur Qalbi Tayibu (Universitas Negeri Makassar, 2016)
This study aims to determine the effect of intelligence, task commitment and self efficacy towards learning outcomes math class X SMA country Bulukumba District of Bulukumba. This type of research is ex-post facto nature of causality. The population in the study were students of Class X SMAN in District Bulukmpa Bulukumba 2014/2015 school year as many as 420 students and 201 students sample, taken by using proportional random sampling. The instrument used consisted of intelligence tests (tests of verbal linguistic intelligence, logical mathematical intelligence and visual-spatial), self-efficacy scale and the scale of task commitment and math achievement test. Data were analyzed using descriptive statistics and inferential statistics that path analysis (path anlysis). The research concludes that: (i) Most students of class X SMA in Bulukumba, have intelligence with the category average, task commitment in learning mathematics with high category, self-efficacy in mathematics with high category and yield learning mathematics are the very low category. (Ii) a variable that significantly that intelligence directly influence the outcome of learning mathematics, self-efficacy directly influence learning outcomes and task commitment directly influence the results of students' mathematics learning, intelligence indirect effect on the result of learning mathematics through task commitment and self-efficacy influential indirectly of mathematics learning outcomes through task commitment.